Mudanças de métodos de custeio e o impacto no sistema de informação gerencial: um estudo qualitativo - Fontoura, Fernando Batista Bandeira da (2009)
The present research consists of identifying the impacts caused in the Management Information System with the change of variable costing method to PEU (Production Effort Unit) in a Study Case, at Bistex Alimentos LTDA, with the data collection made possible by the documental analysis and by the implementation of policy interview with two directors, that have made viable the interpretative data analysis of performing indicators present in the main alterations, after the migration process of this whole process, in a comparative study, surveying controls used in the organization before and after the change of method. Authors as Johnson and Kaplan (1993) approach the managerial accounting, Allora (1996) introduces the costs and managerial production control and Wernke (2008) approaches the application of PEU’s Method, they gave consistence to the operational applicability of this proposal. The main results are in the ordering of information to be fundamental for the PEU use, causing alterations in the organizational culture of the company. The study shows that the implementation of the PEU's method brought changes in the controls of the organization, howver still lacks a holistic vision and integration with the strategic management.